STUDENTS’ PERCEPTIONS OF USING CHATGPT FORENGLISH VOCABULARY AT ELEVENTH GRADE OF FASHION DESIGN IN SMKN 4 JAMBI - Yuli Silwana; Suyadi Suyadi; Efa Silfia (Universitas Batanghari Jambi, 2026)
This study aims to analyze the perceptions of 11th-grade Fashion Design students at SMKN 4 Jambi City regarding the use of ChatGPT as a tool for learning English vocabulary. The research employed a qualitative design with interviews as the main instrument, involving 15 purposively selected students as participants. The collected data were analyzed thematically to identify patterns of students’ perceptions and experiences. The findings reveal that most students perceive ChatGPT positively, highlighting its practicality, efficiency, and ability to enhance motivation and learning autonomy. ChatGPT supports vocabulary acquisition through several mechanisms: repetition (behaviorist learning), contextual explanations (cognitivist learning), and elaboration by connecting new and prior knowledge. Students reported increased confidence in using English vocabulary, particularly in written assignments and informal communication. However, challenges were also noted, including initial confusion in formulating prompts and occasional inaccuracies in responses. In conclusion, ChatGPT demonstrates strong potential as an adaptive and personalized language learning tool, especially for vocational-specific vocabulary. To optimize its effectiveness, students require guidance in prompt formulation and critical evaluation of the information provided.